The principle of equality and the prohibition of discrimination, against equal marriage, in Ecuador - Velasco Velasco, Rebeca; Cabrera Vélez, Juan Pablo; Ruiz Abril, Karina Marianela (Revista Universidad de Guayaquil, 2018)
The present work addresses the theme: "The principle of equality and the prohibition of discrimination, against equal marriage, in Ecuador." The work describes the right to equality, as a fundamental right of the human being, as well as the principle of the prohibition of discrimination, both constitutionalized in Ecuador, therefore of obligatory validity, in any administrative, judicial or even private procedure. Despite this, in practice there are obstacles that must be removed, even in the public sphere fostering open discrimination, as is the case of the impossibility of equal marriage, which is marriage between people of the same sex. In the present work the judicial experience that exists in Ecuador on this subject will be studied.The methodology to be used in the research is deductive, exploratory and descriptive. A qualitative approach will be used, as it is the one of the social sciences and more punctually of the Law.
Keywords: Constitutional law; equality; prohibition of discrimination; equal marriage; discrimination based on gender